LncRNA NEAT1 regulates MMP-16 by targeting miR-200a/b to aggravate inflammation in asthma - Xiao-Jun Duan; Xi Zhang; Niu Ding; Ji-Yan Zhang; Yan-Ping Chen (Taylor & Francis Group, 2021)
Asthma is a common respiratory disease which is characterized by persistent airway inflammation. Abnormal expression of long non-coding RNAs (lncRNAs) is observed in asthma. However, whether lncRNA nuclear-enriched abundant transcript 1 (NEAT1) regulates asthmatic inflammation and its mechanism still needs to be further investigated. The expression levels of inflammatory factors (tumour necrosis factor (TNF)-α, interleukin (IL)-4, IL-13, and IL-10) were detected using reverse transcription quantitative real-time PCR (RT-qPCR) and enzyme-linked immunosorbent assay (ELISA). MTT and flow cytometry assays were employed to determine cell proliferation and apoptosis, respectively. Dual luciferase reporter assay was performed to verify the relationship between miR-200a/b and MMP-16 or NEAT1. NEAT1 silencing markedly reduced TNF-α, IL-4, and IL-13 levels, while elevated IL-10 expression, suppressed cell proliferation, and promoted cell apoptosis. However, NEAT1 overexpression elicited the opposite effects on cell proliferation and inflammation cytokines secretion. What is more, NEAT1 negatively regulated miR-200a/b expression, and MMP16 was a target gene of miR-200a/b. miR-200a/b overexpression suppressed inflammation, cell proliferation, and enhanced cell apoptosis through regulation of MMP16. Moreover, MMP-16 overexpression or miR-200a/b inhibition abolished the regulatory effect of sh-NEAT1 on cell inflammation and apoptosis in BEAS-2B cells. NEAT1 acted as the role of sponge for miR-200a/b to regulate MMP-16 expression, thereby promoting asthma progression, suggesting that NEAT1 might have great potential as therapeutic target for asthma.